2020
DOI: 10.1101/2020.07.01.20144295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitive detection of SARS-CoV-2-specific-antibodies in dried blood spot samples

Abstract: Abstract Importance: Population-wide serological testing is an essential component in understanding the COVID-19 pandemic. The logistical challenges of undertaking widespread serological testing could be eased through use of a reliable dried blood spot (DBS) sampling method. Objective: To validate the use of dried blood spot sampling for the detection of SARS-CoV-2-specific antibodies. Design, setting and participants: Eighty-seven matched DBS and serum samples were obtained from eighty individuals… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…Our sampling strategy, used in an attempt to minimise spectrum bias [ 1 ], may explain the lower sensitivity we observed relative to (for example) the study by Karp et al, in which they observed a 100% sensitivity of DBS compared to plasma, however all their positive samples were taken in the spring and confirmed with PCR; as such, these individuals were more likely to have experienced more severe COVID-19 (as testing was limited to these individuals at the time) and had limited time for antibody levels to decline [ 24 ]. Similar considerations apply when comparing our results with those of Morley et al, who report DBS analytical performance to be comparable to matched serum samples, with a sensitivity of 98.1% and specificity of 100%, when compared to an in-house ELISA which detects Spike glycoprotein antibodies (using 87 samples from 80 volunteers, 37 who had had a previous PCR positive result)[ 25 ].…”
Section: Discussionsupporting
confidence: 82%
“…Our sampling strategy, used in an attempt to minimise spectrum bias [ 1 ], may explain the lower sensitivity we observed relative to (for example) the study by Karp et al, in which they observed a 100% sensitivity of DBS compared to plasma, however all their positive samples were taken in the spring and confirmed with PCR; as such, these individuals were more likely to have experienced more severe COVID-19 (as testing was limited to these individuals at the time) and had limited time for antibody levels to decline [ 24 ]. Similar considerations apply when comparing our results with those of Morley et al, who report DBS analytical performance to be comparable to matched serum samples, with a sensitivity of 98.1% and specificity of 100%, when compared to an in-house ELISA which detects Spike glycoprotein antibodies (using 87 samples from 80 volunteers, 37 who had had a previous PCR positive result)[ 25 ].…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have recently examined the utility of DBS SARS-CoV-2 antibody testing. 1217 However, many of these studies suffer from small sample sizes 12,14,15 or use sample punching/sample extraction procedures that do not make the assay amenable for rapid high-throughput testing. 12,15,16 Furthermore, none of these studies have linked testing with the established newborn DBS screening laboratory infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…This finding confirms that of Morley et al., using a similar ELISA format. 16 To further characterize the performance of our DBS assay, we compared the OD values obtained for DBS specimens analysed using the ELISA to the results from paired serum results obtained using the Healgen Scientific PoCT (IgG and IgM) lateral flow device (detects antibodies to both the spike and nucleocapsid proteins). The results demonstrated good concordance between paired specimens.…”
Section: Discussionmentioning
confidence: 99%
“…DBSs are readily used in analytical assays for viruses such as those for human immunodeficiency virus (HIV) and hepatitis B and C ( Freeman et al, 2018 ; Ross et al, 2013 ; Cassol et al, 1992 ) They are also frequently used for other applications such as screening of neonates, metabolic profiling, pharmacokinetic, forensic and environmental assays ( Freeman et al, 2018 ; Gupta and Mahajan, 2018 ; Bjorkesten et al, 2017 ). The major advantages with using DBS's include: the requirement for a smaller volume of blood, reduced risk of potential bacterial contamination, non-invasive blood collection, easy delivery-to- test centre, low cost and stability for prolonged periods of time with minimal deterioration of analytes ( Morley et al, 2020 ; Freeman et al, 2018 ; Gupta and Mahajan, 2018 ). The additional advantage in the current COVID-19 pandemic include, ensuring patients do not have to attend hospitals and sites with greater risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Tubes were briefly vortexed and incubated overnight at room temperature. DBS eluate was subsequently harvested into a microtube and centrifuged at 10,600 × g for 10 min at room temperature and stored at 4 °C until used ( Morley et al, 2020 ). DBS samples were applied to the assay at a 1 in 4 dilution, resulting in a 1 in 40 overall dilution.…”
Section: Cross Reactivity Of the Elisa With Other Respiratory Diseasementioning
confidence: 99%